2020
DOI: 10.1159/000506308
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Function of Mutual Grooming in Captive Bonobos (Pan paniscus) and Chimpanzees (Pan troglodytes)

Abstract: Social grooming is often exchanged between individuals in many primate species. Rates of bidirectional (or simultaneous mutual) grooming vary across primate species, and its function is not yet fully understood. For example, mutual grooming is frequent in chimpanzees but rare in most primate species including wild bonobos. There are, however, no quantitative data available in captive bonobos. Therefore, through the direct comparison between captive bonobos and chimpanzees, this study aimed to (i) compare the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…during play fighting between individuals can serve as a signal of willingness to invest in the play bout and to prolong it (Immediate Investment Hypothesis; Allanic et al, 2020;Machanda et al, 2014). It has been posited that in chimpanzees the proximate cause of structural and temporal changes of play are partly explained by Heider's Balance Theory (Heider, 1946), according to which group-member would be motivated to change their unbalanced social interactions (in terms of reciprocity) into balanced ones to prolong these interactions (de Nooy et al, 2005;Krackhardt & Handcock, 2007;Moody, 2009;Shimada, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…during play fighting between individuals can serve as a signal of willingness to invest in the play bout and to prolong it (Immediate Investment Hypothesis; Allanic et al, 2020;Machanda et al, 2014). It has been posited that in chimpanzees the proximate cause of structural and temporal changes of play are partly explained by Heider's Balance Theory (Heider, 1946), according to which group-member would be motivated to change their unbalanced social interactions (in terms of reciprocity) into balanced ones to prolong these interactions (de Nooy et al, 2005;Krackhardt & Handcock, 2007;Moody, 2009;Shimada, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Groomer‐groomee relative body orientation (hereafter, relative orientation) was divided into three categories: ventro‐ventral (i.e., groomer‐groomee ventral surfaces faced each other and may have been parallel or within a 90°–180° angle), dorso‐ventral (i.e., the groomer ventral surface faced the groomee dorsal surface and was located parallel or within a 90°–180° angle), and variable (i.e., posture that manifests itself indistinctly as ventral, dorsal or with the ventral surface of the groomer facing the side of the body of the groomee; i.e., the groomer can reach these body sites from front, backside or laterally). The classification of relative orientation on the basis of the groomed body site can be unreliable for some primate species, such as chimpanzees or some Old World monkeys species, in which simultaneous mutual (or bidirectional) grooming is relatively common (Allanic et al, 2020b). Here, an individual can groom dorsal parts of another individual, who in turn grooms back on ventral parts of the first individual, both from a relative ventro‐ventral orientation.…”
Section: Methodsmentioning
confidence: 99%
“…In group-living primates, individuals devote a large proportion of their social time to this behavior, which is heterogeneously distributed not only among the members of a social group, but also among different parts of an individual's body. While grooming distribution among group members has been intensely investigated in primatology (e.g., Cheney, 1992;Di Bitetti, 2000;Dunbar, 2010;Henzi & Barrett 1999;Seyfarth, 1980), the study of factors that determine the preferential selection of some body sites over others during social grooming has received overall little attention (Allanic et al, 2020a(Allanic et al, , 2020bBoccia, 1983;Freeland, 1981). Initial findings suggest that physical factors, such as self-accessibility, hair density, and parasite density may influence the selection of groomed body sites (Boccia, 1983;Zamma, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…recorded continuously the role of each individual: (i) "groomer" where the individual was the only one actively grooming but did not receive any, (ii) "groomee" where the individual was receiving grooming but did not give any, and (iii) "mutual" where both individuals were actively grooming each other. Although a previous study [Allanic et al, 2020b] reported the details of mutual grooming occurrence in captive Pan species, the present study simply treated mutual grooming to code both individuals as "groomer." M.A.…”
Section: Video Codingmentioning
confidence: 99%